Adoption of Six Sigma’s DMAIC to Reduce Complications in IntraLase Surgeries - Åžahbaz, Ibrahim; Taner, Mehmet Tolga; Eliaçik, Mustafa; Kagan, Gamze; Erbas, Engin (International Journal of Statistics in Medical Research, 2014)
Purpose: To show how a private eye care center in Turkey initiated Six Sigma principles to reduce the number of complications encountered during and after femtosecond laser-assisted LASIK (IntraLase) surgeries. Method: Data were collected for five years. To analyse the complications among 448 surgeries, main tools of Six Sigma’s Define-Measure-Analyze-Improve-Control (DMAIC) improvement cycle such as SIPOC table, Fishbone Diagram and, Failure, Mode and Effect Analysis were implemented. Sources and root causes of seventeen types of complications were identified and reported. Results: For a successful IntraLase surgery, experience of the refractive surgeon, patient’s anatomy and calibration of laser power were determined to be the “critical few” factors whereas, patient’s psychology, sterilization and hygiene, and suction-ring’s pressure were found to be the “trivial many” factors. The most frequently occurring complication was found to be subconjunctival haemorrhage. Conclusion: The process sigma level of the process was measured to be 3.3547. The surgical team concluded that sixteen complications (out of seventeen) should be significantly reduced by taking the necessary preventive measures.